School management and organizational culture towards teachers` performance: The perspective of educational transformation - Furkan, Nuril; Adiansha, Adi Apriadi (Journal of Educational Management and Instruction (JEMIN), 2024)
This research addresses the limited deep understanding of the direct impact of the School Movement Management practices on various aspects of teacher performance within the framework of a dynamic organizational culture in the continually transforming educational era. The study aims to examine the influence of school movement management and school culture on the pillars of teacher performance in this era of educational transformation. The research method is quantitative, utilizing a sample of 62 elementary school teachers selected through purposive sampling based on their involvement in the implementation of School Movement Management and their activities within the school's organizational culture. Data was collected through surveys and documentation, including trial testing of the research instruments. Data analysis was conducted using T-test and F-test. The research findings confirmed three points. First, there is an influence of School Movement Management on the performance of elementary school teachers. Second, there is an influence of Organizational Culture on the performance of elementary school teachers. Third, there is a combined influence of School Movement Management and Organizational Culture on the performance of elementary school teachers. This study highlights the importance of collaboration among schools, principals, the community, and supervisors to enhance the competencies of principals in School Movement Management and Organizational Culture. The results provide evidence that both aspects significantly impact teacher performance, supporting more effective human resource management policies in the context of educational transformation